PECULIARITIES OF GOODS LABELING IN UKRAINE - VASIUTA, Viktoriia; KALEMBET, Alina; HVOZDETSKA, Yevgenia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the issue of labeling goods in Ukraine, its features and rules. The main laws of Ukraine regulating the labeling process are analyzed. The concept of "labeling" is disclosed as a type of information about the product that the consumer wants to purchase. The authors note that the Constitution of Ukraine clearly establishes the rule that everyone has the right to access reliable information about the quality of food and household items. Accordingly, no manufacturer should neglect this right of the consumer. Particular attention is paid to the rule of marking in Ukraine exclusively in the Ukrainian language, which is provided for in the Law of Ukraine "On Ensuring the Functioning of the Ukrainian Language as the State Language". The main goals of packaging are considered, namely, the protection of the trade item and the guarantee of its integrity, convenient transportation and storage, and practicality of use, which is important from an environmental point of view. Each company that manufactures or imports products for sale in Ukraine faces labeling requirements. The full-scale invasion of Russia, the aggressor state, into the territory of Ukraine somewhat changed the marking rules for the period of martial law for imported products. Much of the commodity market infrastructure has been damaged or simply destroyed. Related to this are problems with the repackaging of products from abroad. In conditions of increased demand, this is fraught with a shortage of certain types of goods and an aggravation of the crisis in the state and panic of people. To avoid these negative consequences, part of the marking requirements were simplified at the beginning of the war. Currently, the changes apply to both food and non-food products. For food products that have undergone forced changes in the recipe, it is allowed to indicate information that differs from the actual values, but this should not apply to production dates and expiration dates. When marking non-food products, it is not necessary to mark in the Ukrainian language if, due to martial law, this is not possible. An important means of counteracting the spread of counterfeit and counterfeit products, according to the authors, is the label itself. The application of markings and special signs that can be expressive or read by special devices can eliminate the problem of ensuring the quality and safety of products.
Keywords: labeling; consumer; manufacturer; martial law; imported products; product quality; product safety; packaging